Dynamic Young's modulus and glass transition temperature of selected tropical wood species - Hamdan, Sinin; Sedik, Yahya; Jusoh, Ismail; Hasan, Mahbub; Talib, Zainal Abidin (Maney Publishing, 2009)
Dynamic Young's modulus (E d) of selected tropical wood species, namely Dyera polyphylla, Endospermum diadenum, Cratoxylum arborecens, Alstonia pneumatophora, Macaranga gigantea and Commersonia bartramia, used for the study was measured using the free–free flexural vibration method. Young's modulus from three point bending (E 3pb) and compression parallel to grain (E cp) was also studied. The results show that the relationship between E d and E 3pb for all wood species is very significant with the mean value of E d consistently larger than or sometime equal to E 3pb. Surprisingly, the relationship between E d and E cp is not significant except for Alstonia pneumatophora. The dynamic mechanical thermal properties were also investigated using the dynamic mechanical thermal analyser (DMTA). The results showed that the storage modulus of the wood species at –90°C is in the range of 1·48–4·09 GPa with a glass transition temperature ranging from 50 to 70°C.